Microfinance Training : A Magic Wand to Achieve Financial Literacy - Vijaykumar, N. V.; Naidu, Gajendra J. (Arthshastra Indian Journal of Economics & Research, 2018)
Financial literacy is seen as one of the remedies that alleviate the poor by helping them understand finances better. It is perceived to trigger their spirit of entrepreneurship, which in turn helps improve their income. Governments world over have recognized microfinance training as an efficient vehicle to deliver financial literacy to the people at large. However, financial literacy itself is an amorphous concept whose meaning varies depending upon the context and the level of development of countries. Microfinance training is subjected to the vagaries of many variables. Under these circumstances, it was relevant to find out if microfinance training really enables financial literacy. Is this the magic wand which governments are searching for ? This research paper reviewed the literature on the subject to find an answer to this question. A World Bank report on the subject critically noted that while there was enormous research studying the effect of microfinance, there was a dearth of literature studying the effect of microfinance training. The objective of this paper was to assimilate the research done thus far on this subject. The paper initially reviewed the literature on the various hues of financial literacy and later dwelled upon the literature where researchers found evidence to believe that microfinance training enhances financial literacy. Surprisingly, we found a fair amount of research which produced evidence to the contrary and was included in this review. To conclude, a few lessons for policy makers gleaned from the review were also included.